Perbaikan Postur Kerja Proses Muat Kelapa Sawit Berdasarkan Metode Selang Alami Gerak (SAG) - Fadli Arsi; Hilma Raimona Zadry; Feri Afrinaldi (invotek, 2020)
Abstract— The harvesting of palm oil in Indonesia, is still done manually. This research analyzed the movement of the palm oil loading process manually, which risks of Musculoskeletal Disorders (MSDs) to workers. The methods used in this study include observation, interviews, the Nordic Body Map (NBM) Questionnaire, the Natural Range of Motion (ROM), and biomechanical load calculations. NBM is used to identify complaints of the worker’s body parts. The ROM method is used to analyze the risk of body movements when carrying out palm oil loading activities, and the calculation of biomechanical loads is to determine the burden on the worker's body parts. The results showed that there are three parts of the body involved in the process of loading palm oil so that workers often complain of pain, namely the shoulders, neck, and back. The biomechanical load that occurs on the back of the worker is 4866.36 N. This value exceeds the safety limit recommended by the National Institute of Occupational Safety and Health (NIOSH) which is as high as 3400 N. Analysis using ROM found that the existing loading process of oil palm causes shoulders, neck, and back to form angles of 120°, 31° and 12°, respectively. This angle is in the danger zone based on ROM. Improvements are made by changing the work posture in the loading process of oil palm and giving changes to the body angle to 90° on the shoulder, 14° on the neck, and 2° on the back, which are already in the safe zone. The biomechanical load on the back after the improvement also decreased to 3287.38 N